PENGARUH VARIETAS DAN DOSIS PELET Trichoderma harzianum TERHADAP PERTUMBUHAN DAN PRODUKSI CABAI (Capsicum annuum.L) - Eka Fitria; Elly Kesumawati; Bakhtiar Bakhtiar (Jurnal Floratek, 2018)
The use of superior seeds and certified hybrids is one of the efforts to increase the productivity of chili. Absorption of nutrients and water is strongly supported by root growth, with the administration of Trichoderma sp. hence root growth becomes better so that the process of absorption of nutrients and water will also be optimal which also results in the growth and production of chili plants. This study aims to determine the effect of varieties and dosages of T. harzianum pellets as well as their interactions with the growth and production of chili. The design used in this study was a factorial randomized block design (RBD) with 3 replications. The results showed that the treatment of varieties had a very significant effect on the average plant height and canopy width at 20, 40, and 60 DAP, wet stover weight, dry stover weight, fruit length and fruit diameter. Varieties have a significant effect on leaf length, and root length. The growth and production of chili plants is better found in the Lado variety. The dose of T. harzianum has a very significant effect on the average root length and has a significant effect on the average weight of dry stover. The better growth and production of chili plants is found in the administration of 20 g of T. harzianum / plant.